The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1370/afm.1754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Primary Care Team Social Networks on Quality of Care and Costs for Patients With Cardiovascular Disease

Abstract: PURPOSE Cardiovascular disease is the leading cause of mortality and morbidity in the United States. Primary care teams can be best suited to improve quality of care and lower costs for patients with cardiovascular disease. This study evaluates the associations between primary care team communication, interaction, and coordination (ie, social networks); quality of care; and costs for patients with cardiovascular disease.METHODS Using a sociometric survey, 155 health professionals from 31 teams at 6 primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 36 publications
(36 reference statements)
5
67
0
5
Order By: Relevance
“…Our findings are consistent with recent research indicating that team members with lower professional status often experience challenges ''voicing'' their concerns and suggestions to improve unit functioning (Nembhard, Labao, & Savage, 2014). Strategies to improve primary care team member role recognition and clarity facilitate reliable access to interdisciplinary team member expertise, and improved teamwork experiences may hold promise for improving readiness for change.…”
Section: Practice Implicationssupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are consistent with recent research indicating that team members with lower professional status often experience challenges ''voicing'' their concerns and suggestions to improve unit functioning (Nembhard, Labao, & Savage, 2014). Strategies to improve primary care team member role recognition and clarity facilitate reliable access to interdisciplinary team member expertise, and improved teamwork experiences may hold promise for improving readiness for change.…”
Section: Practice Implicationssupporting
confidence: 89%
“…Recent research also highlights the importance of tight team structures and teamwork for members of lower professional status. For example, recent research found that primary care staff are more likely to report that it was not safe to speak up about issues in their work environments (Nembhard, Yuan, Shabanova, & Cleary, 2015). In this study, a greater disconnect between physicians and staff was predictive of lower performance on measures of patients' experiences of access and care coordination.…”
Section: Hypothesismentioning
confidence: 52%
See 1 more Smart Citation
“…To minimize response bias and enhance data validity, the study team assured participants of the confidentiality and anonymity of their responses, that the data would not be shared with the clinic administration and management, and that results would be reported in aggregate format. 27,28 A more detailed description of the study questionnaire is available in Mundt et al 29 …”
Section: Methodsmentioning
confidence: 99%
“…1 In addition, outcomes are significantly better for patients who receive care from teams rather than from individual clinicians, 6 especially when team members constantly interact and have a shared team vision. 7 Thus, primary care is being transformed into care delivered in teams comprised of clinicians from multiple disciplines, including nurse practitioners (NPs) and physician assistants. 8,9 Policy recommendations are supportive of this trend as a means to increase access, improve care, and control costs.…”
Section: Introductionmentioning
confidence: 99%